Replacing This Old House: Certifying and Regulating New Legal Services Providers - Bruce A. Green; M. Ellen Murphy (Washington University Journal of Law and Policy, 2025)
This Article comprehensively examines the decisions that state courts must make, and have made to date, when they certify and regulate new categories of legal services providers: those individuals other than lawyers who are authorized to provide discrete legal services that the laws governing the unauthorized practice of law (UPL) generally reserve to lawyers. In certifying new categories of legal services providers, courts must make an array of interrelated decisions. These include decisions about the rules for educational and testing requirements, the scope of services that legal services providers may offer, the conditions under which they may provide services, and how they will be regulated once certified. Courts may seek guidance in existing models. Courts might find inspiration in the programs established by federal administrative agencies that employ flexible certification requirements for patent agents, design patent agents, and enrolled agents in tax matters—all of whom may independently render discrete legal services, for a fee, in certain administrative proceedings and seem to have done so to the general satisfaction of their clients and the agencies. Alternatively, courts might be influenced by the familiar example of how lawyers are educated, admitted to the bar, and regulated. To date, state courts establishing new categories of legal services providers have been overly influenced by the lawyer licensing process. While lawyers may provide any legal services for which they consider themselves competent, nearly all new categories of providers are strictly limited in their scope of representation. Those permitted to provide broader help with discrete legal matters are subject to overly rigorous and rigid training and testing requirements that make it expensive and time-consuming to gain certification. Rather than allowing providers to serve clients independently as a viable career, courts often forbid legal services providers from charging a fee for their services and require them to be supervised by lawyers in perpetuity, avoiding the need for more thoughtful regulatory oversight. Taken together, these existing requirements make it unlikely that many people will become, continue, and practice successfully as legal services providers. Consequently, courts’ current programs will not fulfill their potential to enable ordinary people to obtain necessary legal help for essential problems concerning their basic human needs. This Article proposes that state courts collaborate in building certification and regulation processes for new categories of legal services providers from the ground up. The components would include: (1) affordable and flexible training focused on the discrete work that the particular providers will be expected to perform competently; (2) education that continues post-certification; (3) pathways to independent provider practice in association with other legal professionals, including lawyers; and (4) post-certification regulation that is proactive as well as reactive.
Keywords: UPLReform; LegalServicesInnovation; AccessToJusticeSolutions